Studies on suitability to incorporate Piper betel leave extract in flavored milk - Patange, Dnyaneshwar D.; Gore, R. B.; Patil, Y. N.; Gaikawad, N. B.; Kalyankar, S. D.; Khedkar, C D (Indian Journal of Dairy Science, 2024)
The present study was carried out to investigate the antioxidant and phenolic potential of Piper betel leaves (PBL)-fortified flavored milk (FM) and thereby assess its storage stability. The FM was prepared by fortifying it with aqueous extract of PBL, sugar, and CMC stabilizer @ 5.15, 10.30, and 0.1 %, respectively followed by its pasteurization (FM1). The bottles were stored at 5±1ºC and compared with control (FM2) i.e. milk without PBL extract. Each sample was evaluated at an interval of 4 days for changes, if any in the sensory attributes, proximate composition, physicochemical properties, antioxidant and phenolic potential, and microbial quality till its sensorial acceptance. It was observed that the sample FM2 recorded flavor score <6.00 on the 9-point Hedonic Scale on the 20th day of storage. The results at this stage revealed that the sample FM1 maintained the score of >7.00 for flavor. It was further seen that the storage period, treatment, and their interaction effect had significant bearing (P<0.05) on viscosity, TBA(total value, HMF content, pH, and proximate composition of the product during the storage, the rate of change was more in a control sample. The viscosity of the FM during storage was altered from 9.62±0.17 to 12.04±0.04 and from 10.85±0.70 to 12.42 ±0.90 cP in FM1 and FM2 sample(s), respectively. The antioxidant bustle and total phenolic content were also decreased during storage, the values on 0 day of storage for FM1 was 5.56±0.53 μM/mL and 5.14±0.32 GAE/mL. Further, there was a sharp increase in standard plate count (SPC) from an initial count of 2.61 ±0.06to 5.00 ±0.04 log10 cfu/ml during storage of 24 days in FM1 and that of the control sample showed increasing trend from 2.61±0.03 to 4.75±0.03 log10 cfu/ml. There was no any coliforms observed in neither the test nor the control samples up to the 20th and 24th day of the storage. Keywords: Piper betel leaves, Flavored milk, Sensory qualities, storage stability, Antioxidant and Phenolic potential.